PIK3CA mutations in ductal carcinoma in situ and adjacent invasive breast cancer. Issue 5 (May 2019) - Agahozo, Marie Colombe; Sieuwerts, Anieta M; Doebar, S Charlane; Verhoef, Esther I; Beaufort, Corine M; Ruigrok-Ritstier, Kirsten; de Weerd, Vanja; Sleddens, Hein F B M; Dinjens, Winand N M; Martens, John W M; van Deurzen, Carolien H M
Abstract : PIK3CA is one of the most frequently mutated genes in invasive breast cancer (IBC). These mutations are generally associated with hyper-activation of the phosphatidylinositol 3-kinase signaling pathway, which involves increased phosphorylation of AKT (p-AKT). This pathway is negatively regulated by the tumor suppressor PTEN. Data are limited regarding the variant allele frequency (VAF) of PIK3CA, PTEN and p-AKT expression during various stages of breast carcinogenesis. Therefore, the aim of this study was to gain insight into PIK3CA VAF and associated PTEN and p-AKT expression during the progression from ductal carcinoma in situ (DCIS) to IBC. We isolated DNA from DCIS tissue, synchronous IBC and metastasis when present. These samples were pre-screened for PIK3CA hotspot mutations using the SNaPshot assay and, if positive, validated and quantified by digital PCR. PTEN and p-AKT expression was evaluated by immunohistochemistry using the Histo-score (H-score). Differences in PIK3CA VAF, PTEN and p-AKT H-scores between DCIS and IBC were analyzed. PIK3CA mutations were detected in 17 out of 73 DCIS samples, 16 out of 73 IBC samples and 3 out of 23 lymph node metastasis. We detected a significantly higher VAF of PIK3CA in the DCIS component compared to the adjacent IBC component ( P = 0.007). The expression of PTEN was significantly higher in DCIS compared to the IBC component in cases with a wild-type (WT) PIK3CA status ( P = 0.007), while it remained similar in both components when PIK3CA was mutated. There was no difference in p-AKT expression between DCIS and the IBC component. In conclusion, our data suggest that PIK3CA mutations could be essential specifically in early stages of breast carcinogenesis. In addition, these mutations do not co-occur with PTEN expression during DCIS progression to IBC in the majority of patients. These results may contribute to further unraveling the process of breast carcinogenesis, and this could aid in the development of patient-specific treatment.